Asian development outlook forecast accuracy 2007-2016 - Benno Ferrarini (Asian Development Bank (ADB), 2019)
This is done in relation to the benchmark of World Economic Outlook (WEO) projections by the International Monetary Fund. Amid much heterogeneity across countries and years, it has been found that ADO and WEO projections overlap quite closely. Both are inaccurate, especially during crisis years, suggesting that forecasters struggle to come up with reliable forecasts. Projections only sharpen when additional data and evidence become available over time and are incorporated during quarterly revisions.
Keywords: E17; E37; 330; Asian Development Bank; Asian Development Outlook; International Monetary Fund; macroeconomic forecasts; World Economic Outlook